Determination of Agronomic Characteristics as Selection Criteria in Potato Crossing Lines - Ishartati, Erny; Sufianto, Sufianto; Zakia, Aulia; Mejaya, Made Jane; Madianto, Rudy (PLANTA TROPIKA, 2022)
Vegetative propagation of potato decreases variation in commercially cultivated varieties. Induction of variability in potatoes is needed for crop improvement. Selection is selecting the best individual plants based on the desired characteristics, which will be effective when suitable characteristics are used. The objective of this study was to determine the agronomic characteristics for the selection of potato crossing lines through heritability, genetic variability, and genotypic correlation. The experiment was conducted at the Greenhouse, Sumber Brantas Village, Batu City, East Java. The materials used were 30 potato lines resulting from LJPRSD1 x AP-4. This study was arranged in a complete randomized design (RCD) with three replications. The agronomic characteristics observed include plant height, stem diameter, number of leaves, the diameter of tuber, number of tubers, tuber length, weight per tuber, starch, and glucose. Almost all characteristics observed showed high heritability values, except stem diameter and tuber length. The genetic variability in stem diameter, tuber diameter, and tuber length was low, whereas the genetic variability in other characteristics was slightly low. The genotypic correlation was significant between characteristics, except between starch content and weight per tuber. Meanwhile, the agronomic characteristics used for selection are plant height, diameter of tuber, number of tubers.